Fate of engineered cerium oxide nanoparticles in an aquatic environment and their toxicity toward 14 ciliated protist species. (May 2016) - Zhang, Wei; Pu, Zhichao; Du, Songyan; Chen, Yongsheng; Jiang, Lin
Abstract: The potential environmental impacts of engineered cerium oxide nanoparticles (CeO2 NPs) on aquatic organisms have remained largely unknown. Therefore, the laboratory study featured herein was performed to determine the fate of CeO2 NPs in an aquatic environment and their toxicity towards 14 different ciliated protist species at a specified population level. An investigation of 48 h aggregation kinetics in the Dryl's solution showed the CeO2 NPs to be relatively stable. The pH values in three test medium were too far away from PZC, which explained the stability of CeO2 NPs. CeO2 NPs generally elicited more toxicity with increasing NP concentration, following certain dose-response relationships. Nano-CeO2 resulted in greater toxicity in a particle state than when added as bulk material. LC50 values showed a negative correlation with the surface-to-volume ratio for these protists, suggesting that surface adsorption of CeO2 NPs might contribute to the observed toxicity. Additionally, acute toxic responses of 14 ciliated protist species to CeO2 NPs were not significantly phylogenetically conserved. The results of these observations provide a better insight into the potential risks of CeO2 NPs in an aquatic environment. Highlights: Acute toxicity of CeO2 NPs toward 14 ciliated protist species was first assessed. 48 h aggregation kinetics in Dryl's solution showed CeO2 NPs were relatively stable. CeO2 NPs generally elicited greater toxicity in a particle state than a bulk state. LC50 values were negatively correlated with surface-to-volume ratio of the protists. LC50 values of 14 protist species were not significantly phylogenetically conserved. Abstract : This study is the first to demonstrate the fate of CeO2 NPs in an aquatic environment and their acute toxicity toward 14 ciliated protozoans.